EFEKTIVITAS METODE ELEKTROKOAGULASI DALAM MENURUNKAN KANDUNGAN COD DAN TSS PADA AIR LIMBAH - Jubaidi, Jubaidi (JURNAL MEDIA KESEHATAN, 2013)
This study aims to determine the effectiveness of electro coagulation in reducing the content of COD and TSS in hospital wastewater of dr M. Yunus Bengkulu. This type of research is the study of pre experimental pretest posttest design without control group, the sample in this study were 36 samples. Primary data was analyzed by Annova test and followed by LSD test. The results showed that there was a decrease of 58.55% content of COD and TSS content of 63.20%, LSD test results demonstrate the value of p = 0.000, which means there is a real difference in reducing the content of the wastewater TSS Hospital dr. M.Yunus Bengkulu.